1976
DOI: 10.1099/0022-1317-31-2-231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Swine Vesicular Disease Virus and Coxsackie B5 Virus by Serological and RNA Hybridization Methods

Abstract: SUMMARYThe relatedness of swine vesicular disease virus (SVDV) and Coxsackie B5 virus has been studied by virus neutralization and immunodiffusion tests and by hybridization of the virus RNAs. Clearly defined differences between the two viruses were found by the three methods. Isolates of SVDV from several countries were very closely related but could be differentiated. Recent isolates of Coxsackie B5 virus also appeared to be similar but clear differences could be detected between these and the prototype (Fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Subsequently, outbreaks were seen in Hong Kong in 1971 (Mowat et al, 1972) and in Europe and Japan during 1972-1975(Brown et al, 1976. Following eradication campaigns, SVD was eliminated from most of Europe by the mid 1980s, apart from Italy, where the disease has continued to persist until the present day.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, outbreaks were seen in Hong Kong in 1971 (Mowat et al, 1972) and in Europe and Japan during 1972-1975(Brown et al, 1976. Following eradication campaigns, SVD was eliminated from most of Europe by the mid 1980s, apart from Italy, where the disease has continued to persist until the present day.…”
mentioning
confidence: 99%
“…MAR mutants were produced using each of MAbs C29, C70, C74, 5B7, 4H3 and 5D9 and were characterized by virus neutralization (VN) assays (Brown et al, 1976) and by ELISA. The percentage binding of MAbs to MAR mutants in ELISA was expressed as a percentage of the binding to the parental strain using an adaptation of the FMD strain characterization ELISA of Samuel et al (1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the antigen preparation appears to have little bearing on the specificity of those tests in which the antigen is allowed to adsorb directly on to a solid phase. Even purified virus prepared by treatment with sodium lauryl sulphate to remove provirions (Brown et al, 1976) shows heterotypic activity when used under such conditions (Hannington et al, 1983). On the other hand, Katze and Crowell (1980) have shown that the type-specificity of purified coxsackie B viruses is preserved when they attach to a solid phase previously coated with specific 'capture' antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the aetiological agent of an animal disease emerging in 1966, swine vesicular disease, is antigenically related to coxsackievirus type B5 (Graves, 1973;Brown et al, 1976) suggests that group B coxsackieviruses may undergo antigenic variation associated with marked changes in host tropism and pathology. Furthermore, a diabetogenic strain of coxsackievirus B4 (CBV-4) isolated from a human pancreas was more closely related antigenically to a diabetogenic strain selected by passage of the prototype CBV-4 strain in beta cells than to the prototype virus itself (Yoon et al, 1979).…”
Section: Introductionmentioning
confidence: 99%